2020
DOI: 10.1002/jobm.202000522
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of volatile organic compounds produced by Bacillus subtilis CL2 on pathogenic fungi of wolfberry

Abstract: Bacillus subtilis strain CL2 is antagonistic to wolfberry postharvest pathogenic fungi. In this study, we isolated and screened this strain for in vitro experiments. The result of the two-sealed-base-plates method revealed that volatile organic compounds (VOCs) emitted from the strain CL2 inhibited the hyphal growth of four pathogenic fungi Mucor circinelloides LB1, Fusarium arcuatisporum LB5, Alternaria iridiaustralis LB7, and Colletotrichum fioriniae LB8. After exposure to VOCs for 5 days, the hyphal growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Pathogenic fungi Phytophthora capsici (ACCC 37132), Colletotrichum capsici (ACCC 36946), F. oxysporum (ACCC 39326), B. cinerea (ACCC 37347), Rhizoctonia solani (ACCC 38870), F. graminearum (ACCC 39334) were obtained from Agricultural Culture Collection of China, Beijing. F. annulatum (MT 434004), Talaromyces tumuli (MT 434003), Colletotrichum fioriniae (MN 944922), and F. arcuatisporum (MN 944920) were isolated from disease plants and all pathogenic strains were stored in the laboratory ( Ling et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogenic fungi Phytophthora capsici (ACCC 37132), Colletotrichum capsici (ACCC 36946), F. oxysporum (ACCC 39326), B. cinerea (ACCC 37347), Rhizoctonia solani (ACCC 38870), F. graminearum (ACCC 39334) were obtained from Agricultural Culture Collection of China, Beijing. F. annulatum (MT 434004), Talaromyces tumuli (MT 434003), Colletotrichum fioriniae (MN 944922), and F. arcuatisporum (MN 944920) were isolated from disease plants and all pathogenic strains were stored in the laboratory ( Ling et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The method used for identifying VOC components of B. velezensis L1 is consistent with that described in our previous study (Ling et al, 2021). Then, 10 μl of the bacterial suspension of strain L1 was inoculated into a 20-mL headspace vial containing 5 ml of solid LB medium.…”
Section: Identification Of Vocsmentioning
confidence: 97%
See 1 more Smart Citation
“…No adverse health effects have been reported at the level of 2,3-butanedione added to foods ( Morgan et al, 2016 ). Our latest study found that endophytic Bacillus subtilis CL 2 could significantly inhibit postharvest pathogens of wolfberry by producing VOCs, and the composition and function test of VOCs showed that 2,3-butanedione is the main active ingredient ( Ling et al, 2021 ). 2,3-butanedione has always been used as an edible additive, and it is safe and harmless ( Hallagan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given their high perishability, high water content, and susceptibility to damage and rot [ 7 ], fresh goji berries are generally only available in areas where they are cultivated. This is also due to the lack of information on the goji berry’s postharvest behavior and storage recommendations [ 8 ]. Dipping in lecithin solution [ 9 ] and edible coating applications based on lotus leaf extract [ 7 ] have been studied to prolong the shelf-life of goji.…”
Section: Introductionmentioning
confidence: 99%